Surface plasmon enhanced infrared photodetection - Tong, Jinchao (2020)
Infrared photodetectors have been used extensively in biomedicine, surveillance, communication and astronomy. How-ever, state of the art technology based on III-V and II-VI compounds still lacks excellent performance for high-temperature operation. Surface plasmon polaritons (SPPs) have demonstrated their capability in improving the lightdetection from visible to infrared wave range due to their light confinement in subwavelength scale. Advanced fabrication techniques such as electron-beam lithography (EBL) and focused ion-beam (FIB), and commercially available numerical design tool like Finite-Difference Time-Domain (FDTD) have enabled rapid development of surface plasmon (SP) en-hanced photodetectors. In this review article, the basic mechanisms behind the SP-enhanced photodetection, the differ-ent type of plasmonic nanostructures utilized for enhancement, and the reported SP-enhanced infrared photodetectors will be discussed.